The eIF4A inhibitor silvestrol sensitizes T-47D ductal breast carcinoma cells to external-beam radiotherapy. (September 2020) - Webb, Thomas E.; Davies, Marc; Maher, John; Sarker, Debashis
Highlights: Treatment of T-47D breast cancer cells with silvestrol sensitised them to radiation. 1 nM silvestrol caused a 34% reduction in cells exposed to 2 Gy. Clonogenic assays revealed silvestrol had a dose modifying factor of 1.4. Radiation was delivered to the tissue culture plate using a clinical LINAC machine. Abstract: Purpose: eIF4A is an RNA helicase that forms part of the machinery of translation initiation. Proteomic analysis demonstrated eIF4A expression to be at least two-fold greater in a radioresistant derivative of T-47D breast cancer cells compared to parental cells. Inhibition of eIF4A has previously been shown to re-sensitize lymphomas to chemotherapeutic agents that cause DNA damage. The objective of this work is to investigate whether inhibition of eIF4A using silvestrol sensitizes breast cancer cells to radiotherapy in tissue culture, using T-47D as a model system. Methods and materials: T-47D cells were incubated in medium containing 0 nM to 1 nM silvestrol either for 24 h prior to irradiation at 0 Gy to 10 Gy, delivered by linear accelerator (LINAC) or continually for six days post irradiation. MTT viability and clonogenic assays were used to quantify response. Results: Pre-treatment of T-47D cells with 1 nM silvestrol caused a 34% reduction ( p = 0.014) in viability on irradiation at 2 Gy compared to treatment with a DMSO control, as assessed by MTT assay. Maintenance of cells in 1 nM silvestrol for six days following irradiation at 2 Gy caused a 58% reduction ( p = <0.001) in tumor cell viability. Clonogenic assays performed on cells maintained in 1 nM silvestrol following irradiation showed a dose modifying factor (DMF) of 1.4 ( p = <0.001, one-way ANOVA). Conclusions: Low concentrations of silvestrol sensitize T-47D breast cancer cells to radiation with minimal effects on unirradiated cells. This highlights the possible usefulness of eIF4A inhibition in potentiating radiation-induced damage at the tumor site without causing systemic toxicity.